Perceptions and Barriers to Human Papillomavirus Vaccination and Cervical Cancer Screenings: A Survey Study of Underserved Populations in North Texas - Sofia Eva Olsson; Sameep Shah; Erin Haase; Kelly Pagidas (Public Health Challenges)
ABSTRACT Background Human papillomavirus (HPV) is a common cause of cervical cancer along with several other neoplasms. With the availability of HPV vaccination and cervical cancer screenings, it is more likely for cervical cancers to be prevented or caught early in their course. However, there are disparities and barriers preventing all individuals from obtaining proper preventative care. Methods An online survey analyzing compliance, barriers, and subjective perceptions of HPV vaccination and cervical cancer screening was distributed via flyers. These were placed in the half of zip codes with lowest median income in Fort Worth, Texas. Results Respondents with non‐White race, income of $40,000 or less, and a maximum education of high school or less were 4.24, 3.2, and 1.2 times more likely to have incomplete HPV vaccination, respectively. Respondents with an income of $40,000 or less and a maximum education of high school were 3.2 and 2.6 times more likely to be overdue for cervical cancer screening, respectively. The most common barrier for HPV vaccination was lack of knowledge, and for cervical cancer screening, it was cost. Most respondents felt as though cervical cancer screening allows for early cancer detection and decreased mortality but also endorsed feelings of pain, embarrassment, and fear of the test. Conclusions HPV vaccine and cervical cancer screening non‐compliance is likely multifactorial, including lack of knowledge and cost. Interventions such as increased access to pediatric care and increased opportunities for free preventative healthcare may be helpful in both reducing stigma and improving access to care.